Relationship of uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide with acute cerebral infarction - Li,Gang (2021)
SUMMARY OBJECTIVE: The objective was to study the relationship of serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels with acute cerebral infarction. METHODS: A total of 96 acute cerebral infarction patients were divided into small, middle, and large infarct size groups based on the size of infarct focus and mild, moderate, and severe infarction groups based on the evaluation criteria of nerve defect degree. In addition, 75 healthy people were selected as the control group. The serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels of all subjects were detected. RESULTS: The serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels in the acute cerebral infarction group were significantly higher than the control group (p<0.05). Compared with the small infarct size group, each index in middle and large infarct size groups was significantly increased (p<0.05). Compared with the middle infarct size group, each index in the large infarct size group was significantly increased (p<0.05). The serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels in moderate and severe infarction groups were significantly higher than the mild infarction group (p<0.05). Compared with the moderate infarction group, each index in the severe infarction group was significantly increased (p<0.05). The serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels were positively correlated with the infarct size and nerve defect degree (p<0.05). CONCLUSIONS: The serum uric acid, C-reactive protein, and N-terminal pro-B-type natriuretic peptide levels are closely correlated with the occurrence and development of acute cerebral infarction. The detection of these indexes has significance for understanding the severity of acute cerebral infarction, guiding the individual treatment scheme, and evaluating the prognosis.